Estimation of aerosol altitude from reflectance ratio measurements in the O2 A-band - Dubuisson, P.; Frouin, R.; Duforêt, L.; Dessailly, D.; Voss, K.; Antoine, David (SPIE, 2006)
A methodology is presented to estimate aerosol altitude from reflectance ratio measurements in the O2 absorption Aband. Previous studies have shown the impact of the vertical distribution of scatterers on the reflectance ratio. The reflectance ratio is defined as the ratio of the reflectance in a first spectral band, strongly attenuated by O2 absorption, to the reflectance in a second spectral band, minimally attenuated. First, a sensitivity study is performed to quantify the expected accuracy for various aerosol loadings and models. An accurate, high spectral resolution, radiative transfer model that fully accounts for interactions between scattering and absorption is used in the simulations. Due to their adequate spectral characteristics, POLDER and MERIS instruments are considered for simulations. For a moderately loaded atmosphere (i.e., aerosol optical thickness of 0.3 at 760 nm), the expected error on aerosol altitude is about 0.3 km for MERIS and 0.7 km for POLDER. More accurate estimates are obtained with MERIS, since the spectral reflectance ratio is more sensitive. Second, the methodology is applied to MERIS and POLDER imagery. Estimates of aerosol altitude are compared with lidar profiles of backscattering coefficient acquired during the AOPEX-2004 experiment. Retrievals are consistent with measurements and theory. These comparisons demonstrate the potential of the differential absorption methodology for obtaining information on aerosol vertical distribution.